(untitled) - Harris, Phil (London, 1980)
In this new edition of "An Introduction to Law", now established as one of the leading student introductions, the emphasis continues to be on understanding law and the legal system as living institutions within society. At the same time, the coverage of the legal system is combined with a clear account of legal concepts. The fourth edition incorporates much new material, in particular on contract, tort, dispute-resolution and land-use, and the coverage of the European dimension of English law has been considerably expanded.
Keywords: Law; Great Britain